Taxonomic review of the genus Osbornellus Ball (Hemiptera: Cicadellidae) in Central America - Domínguez, Edwin; Godoy, Carolina (Zootaxa, 2010)
A taxonomic review of the genus Osbornellus (Hemiptera: Cicadellidae) in Costa Rica revealed the presence of 48 species, of which 37 are described as new and six are new records for the country. A key for the identification of Osbornellus species of Costa Rica is provided. Osbornellus lacunis DeLong and Martinson is synonymized with Osbornellus blantoni Linnavuori and Osbornellus separatus DeLong is synonymized with Osbornellus pallidus.